Performance of hilly and naked neck hilly chicken at Naikhongchari of Bangladesh (Bangladesh Journal of Animal Science, 2022)
A study was conducted to evaluate the production and hatching performances of hilly chickens and naked neck (NN) hilly chickens at the hilly areas of Naikhongchari regional station research farm of Bangladesh Livestock Research Institute (BLRI). The experimental chickens were reared in an open-sided poultry house under an intensive management system for a period of 18 month. The birds were allowed to take feed and clean drinking water ad libitum. Data on productive and reproductive performances of hilly and NN hilly chickens were recorded regularly. Result revealed that no significant (P>0.05) difference on body weight of day old, 2nd weeks and 4th weeks of age but significantly (P